Tylko ten jeden przykład Proszę o pomoc



Tylko Ten Jeden Przykład Proszę O Pomoc class=

Odpowiedź :

Magda

Odpowiedź:

[tex]\sqrt{8-\frac{8}{9}}-\sqrt{(\frac{8}{9})^2}=\sqrt{\frac{72}{9}-\frac{8}{9}}-\frac{8}{9}=\sqrt{\frac{64}{9}}-\frac{8}{9}=\frac{8}{3}-\frac{8}{9}=\frac{24}{9}-\frac{8}{9}=\frac{16}{9}=1\frac{7}{9}[/tex]

Heh

Odpowiedź:

[tex]\sqrt{8-\frac{8}{9}}-\sqrt{(\frac{8}{9})^{2}}=\\\\=\sqrt{\frac{72}{9}-\frac{8}{9}}-\sqrt{(\frac{8}{9})^{2}}=\\\\=\sqrt{\frac{64}{9}}-\sqrt{(\frac{8}{9})^{2}}=\\\\=\sqrt{(\frac{8}{3})^{2}}-\sqrt{(\frac{8}{9})^{2}}=\\\\=\frac{8}{3}-\frac{8}{9}=\\\\=\frac{24}{9}-\frac{8}{9}=\\\\=\frac{16}{9}=\\\\=1\frac{7}{9}[/tex]

Szczegółowe wyjaśnienie: